Studying the influencing factors on the required quantity of food commodities in Tartous - محسن جحجاح,; محمود حسين, (Latakia University Journal -Biological Sciences Series, 2023)
The aim of the research is to study the relationship between the level of food commodity prices and consumer income as independent variables and the amount of materials consumed as a dependent variable. The research was carried out in Tartous Governorate, where a random sample of consumers was taken and data was collected about the consumed quantities of food commodities and their prices, in addition to collecting information on the demographic characteristics of consumers such as gender, age and income by designing a questionnaire form where the questionnaire consisted of the following axes: Personal information axis, axis Income distribution, the axis of the consumed quantity of food commodities, the axis of the effect of price on consumer decision and behavior. This research relied on the descriptive analytical approach, to study the demographic characteristics of the research sample by designing appropriate tables and calculating arithmetic averages, frequencies and percentages, in addition to analyzing and characterizing consumer behavior by analyzing the answers to the questionnaire questions after ensuring their validity for analysis by calculating the (Alpha Konbach) index. The inferential statistical method was also adopted to test the research hypotheses. Expenditure on (olive oil) occupied the greatest relative importance among the food commodities in question, which is considered one of the basic commodities that cannot be dispensed with and because of the dependence on it for cooking after the sunflower oil became equivalent to the price of olive oil. Potatoes occupied the second place in terms of relative importance in consumption, and broiler meat ranked third among the members of the studied sample. The results of the research showed a statistically significant effect of income on the consumed quantities of the food commodities in question. The results showed a statistically significant effect of the price variable on the consumed quantities of food commodities.